Kepribadian Tokoh Perempuan dalam Novel Bertema Konflik Aceh - Mohd Harun; Mimi Suhaimi (HISKI, 2017)
This study described the personalities of female characters within three novels with Acehnese conflict as theme that was based on the Sigmund Freud psychoanalytical perspective. The data resources encompassed three novels: Tunggu Aku di Ulegle, Seulanga, and Bidadari Hitam. Qualitative approach was used as the study on psychological aspect of literature. The result indicated several matters. In the novel of Tunggu Aku di Ulegle, ego could not control the desire of id, which was too strong for Fatma, Hamidah, and Umi. Fatma and Umi at last regretted all of their actions (superego). Then, in the novel of Seulanga, ego successfully controlled id that prevented regret by the character (superego). Upon the character of Cadine, ego took the correct act, which referred to the action of arranging strategies to achieve the objectives of id. However, ego did not performed the action in accordance of the principles set by superego, which made her regretted at last (superego). Then, upon the character of Sadina, ego could not control the quite strong id, which made ego committed aggressive actions in accordance to the principles of id. Even so, Sadina regretted her actions. Finally, in the novel of Bidadari Hitam, the character of Inong acted as her desire, which was impulsive and amoral. Nevertheless, she regretted her actions (superego). On the other hand, upon the characters of Fitriah and Mak Santan, ego could control the desire of id quite well. Furthermore, ego also acted in appropriate to the principles of superego.